STUDI PERANCANGAN PERBANDINGAN KONSTRUKSI DINDING PENAHAN TANAH KANTILEVER DAN COUNTERFORT PADA RUAS JALAN SOEKARNO-HATTA KM 2 STA 0+000-0+050 KABUPATEN KUTAI TIMUR - SAPUTRO, DWI (KURVA S JURNAL MAHASISWA, 2017)
East Kutai Regency is one of the regencies in East Kalimantan Province. The capital cityof the regency is located in Sangatta which has an area of 35,747,50 kmÂ² which has greatpotential to experience avalanches, especially on road network. The purpose of this research is toknow the comparison of Kantilever type of retaining wall and Counterfourd on Jalan SoekarnoHattaKm 2 STA 0 + 000 - 0 + 050 Sangatta city in terms of implementation and security.Limitations of this research problem, The location of the research in Soekarno-Hatta Road Km 2STA 0 + 000 - 0 + 050 Sangatta city, excluding the implementation method, and calculation onlythe pressure and stability of shear, rolling and collapse.Method of data return that is primary and secondary data, primary data that istopographic data, boring data, data sondir then do with laboratory test and secondary data fromplanning data. Converse - Labarre Formula.Based on the results of the laboratory results obtained no effect of pore water in the soil.Furthermore, the slope stability analysis using the fellenius method with SF (Safety factor) 2,11>1, is declared stable slope. Calculation of cantilevered cantilever wall structure Rankine methodcan be active soil pressure value Ka = 0.44 and passive soil pressure Kp = 2.27 and Coulumbmethod in Ka value = 0.39 and Kp = 3.49. Calculation of bolsters by Rankine Fguling = 2.35 andaccording to Coulumb Fguling = 2.7. Calculation of shear forces in can Î£Rh = 134 , 99 kN / m,according to Rankine Fgeser = 2.34 and according to Coulumb Fgeser = 2.81. The ultimatesupport capacity according to Rankine is qult = 333,95kN / m2, the safety factor to the collapse ofthe carrying capacity F = 4.91, and according to Coulumb q ult = 394,357kN / m2 with the valueof the carrying capacity F = 6.3. single pole for cantilevered retaining wall with CPT 517,05kN,SPT 552,829 kN, 6404,22kN group pole, 12 poles and single pile for retaining walls Counterfortvalue of group pole 7422,59 kN, number of pile 14 fruit.The analysis result can be concluded the ratio of Cantilever and Counterfort to thestability of bolsters by Rankine 2.35 <2.42 and according to Coulumb 2.66 <2.74. Shear stabilityby Rankine 2.34 <2.50 and according to Coulumb 2.81 <3. Stability of collapse according toRankine 4.91> 3.74 and according to Coulumb 6.31> 4.73.